Prostate artery embolisation: an all-comers, single-operator experience in 159 patients with lower urinary tract symptoms, urinary retention, or haematuria with medium-term follow-up. Issue 7 (July 2019) - Thulasidasan, N.; Kok, H.K.; Elhage, O.; Clovis, S.; Popert, R.; Sabharwal, T.
Abstract : AIM: To describe the authors' experience with prostate artery embolisation (PAE) to treat lower urinary tract symptoms (LUTS) due to benign prostatic hyperplasia (BPH) or refractory haematuria of prostatic origin (RHOPA). MATERIALS AND METHODS: PAE was attempted in 159 patients. Procedural details, pre/post-PAE symptom scores, and pre/post-PAE magnetic resonance imaging (MRI) data were recorded. Statistical analysis was performed to determine clinical outcomes and factors predicting clinical success. RESULTS: Technical success was achieved in 156 patients. In patients with LUTS, the International Prostate Symptom Score (IPSS) improved from a mean of 22 at baseline to 9.5 at 6-months post-PAE, then to 10.7, 10, 11.3, and 11 at 1, 2, 3, and 4 years. The quality of life (QoL) score improved from 4.6 at baseline to 2, 2.2, 2.4, 3.1, and 2.5 at the same time points. The International Index of Erectile Function (IIEF-5) scores remained stable. There was no significant difference in IPSS between bilateral or unilateral embolisation to 2 years, or between BPH alone or BPH with biopsy-proven prostate cancer to 3 years post-PAE. Percentage improvement in IPSS at 1 year correlated with percentage reduction in prostate volume on first post-PAE MRI. Percentage improvement in IPSS at 3 years correlated with initial IPSS. PAE facilitated urinary catheter removal in 13/24 patients in retention. PAE controlled bleeding in 12/12 patients with RHOPA. CONCLUSION: PAE is safe and effective in the management of symptomatic BPH. Patients with the highest baseline IPSS and reduction in prostate volume on first post-PAE MRI are likely to derive most benefit from embolisation. Highlights: PAE improves LUTS due to BPH out to at least 4 years post-embolisation. PAE equally effective for LUTS in patients with concurrent prostate cancer. Prostate volume reduction on post-PAE MRI predicts clinical outcome. Patients with severe LUTS likely to derive long-lasting benefit from PAE. PAE is effective in treating intractable haematuria of prostatic origin.